PENGARUH DIALEKTOLOGI DAN CAMPUR KODE MELALUI KAJIAN SOSIO DAN EKOLINGUISTIK TERHADAP KEMAMPUAN BAHASA ARAB MAHASISWA - Rohmah, Lailatur; Maulana, Asep; Anam, Syamsul (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: The phenomenon of code mixing at Student Entrepreneur Islamic Boarding School of Nurul Islam 2 (PPME Nuris 2), especially in the AIQ program in which students are required to speak Arabic although they have not mastered all the vocabularies yet, so that the mixing code between Arabic and regional languages, including Javanese or Madurese, influences the dialect of every University student of this program. Aims: This research is expected to answer the questions about what influences the appearance of code mixing and dialectology, the process of forming code mixing and dialectology, and the influence of dialectology and code mixing on students. Methods: This research used a qualitative approach with a case study as its research type. The data collection techniques used were observation, interviews, and triangulation around the Student Entrepreneur Islamic Boarding School of Nuris 2 using participatory observation, guided interviews, data triangulation, and sources. Results: This study revealed that the emergence of code-mixing and dialectology among students is influenced by internal and external factors, including their environment and personal experiences. This process is shaped by the diverse regional backgrounds of the students, their social interactions, and academic demands. Dialectology and code-mixing contribute positively to students' Arabic-speaking proficiency, as code-mixing is part of language acquisition, helping students develop confidence in speaking a second language fluently and accurately. However, it also challenges Arabic grammar, as excessive code-mixing can disrupt linguistic structures, making the language appear less formal and potentially hindering proper learning. Implications: This study makes significant contributions to socio-linguistic and ecolinguistic studies, especially regarding how social interactions and environmental factors influence the students’ use of Arabic. It deepens understanding of social dynamics that influence language, such as code-mixing usage in multilingual conversation.